An Experimental Study to Evaluate the Effects of Adenosine on Intraocular Pressure in Conscious Albino Rabbits - Shrestha, Rashmi; Khadka, Anjan; Singh, Nishith (Medical Journal of Shree Birendra Hospital, 2016)
Introduction: Glaucoma is a common problem globally which can lead to irreversible blindness. It is characterized by progressive optic nerve damage. Though its definition doesn’t include elevated intraocular pressure but it is known that elevated intraocular pressure is the main culprit behind development of glaucoma. There are various medical and surgical treatment for glaucoma but none are without risk. None of the existing modalities leads to desired control of intraocular pressure and combined approach is needed for the treatment. The study is aimed to evaluate the activity of adenosine, a vasoactive agent, on intraocular pressure in rabbits as the search of newer agents for treatment and prevention of glaucoma. Methods: The study was carried out in albino rabbits using two experimental models viz. water loading model (acute) and steroid induced model (chronic) to induce glaucoma. Intraocular pressure lowering effects of adenosine was studied in both models. IOP was measured with Schiotz tonometer. The intraocular pressure measurement was converted in to mm of Hg by using a IOP conversion chart. Results: Adenosine significantly prevented the acute rise in intraocular pressure in water loading acute model of glaucoma and significantly reduced intraocular pressure in chronic dexamethasone induced glaucoma model. The maximum mean difference in IOP between control and adenosine treated eyes were 15.29% in intragastric tap water loading model. The maximum IOP reduction was 33.52% in chronic model induced by dexamethasone (0.1%). Conclusion: Adenosine reduces the intraocular pressure in rabbits with experimentally induced glaucoma. This activity of adenosine needs to be confirmed and validated through further experimental and clinical studies.